Effect of drilling parameters on Neem wood veneer epoxy composites using grey relational analysis. (2020) - Jaiprakash, M.; Nagamadhu, M.; Karthikeyan, K.; Kiran,; shariff, Mudabbir; Mohan Kumar, G.C.
Abstract: In recent trend the composites based wood are replacing the normal wood and other materials in various fields. The wood composites have cosmic properties like cheaper in cost, denser, free from defect, they can be machined in any way to make desired output product. This paper is all about investigation of wood properties and its behavior for drilling process. Drilling is one of the universal machining process that being carried out in the world .The purpose of drilling is to remove the excess of material from the work piece (specimen) to produce a hole and drilling is the primary process that need to be carried on the specimen to perform other machining operation (boring, reaming and tapping) as drilling got various level of importance in different applications, studying about drilling process and its parameter on different materials is important. This paper is all about the analysis of different drilling parameters such as feed rate (mm/min), spindle speed (rpm), Drill diameter on the quality of drilled hole. To study these factors Grey relation technique and Taguchi analysis is implemented. The result shows that feed rate is the major influencing parameter when compared to other cutting parameter and by selecting the optimal value, the quality of the drilled hole can be improved